Respon Pemberian Kompos Azolla microphylla Dan Arang Sekam Terhadap Pertumbuhan Dan Hasil Bawang Merah (Allium ascalonicum L.) Var. Bima Brebes - Nurjanah, Mita; Historiawati, Historiawati; Novianto, Esna Dilli (JURNAL VIGOR, 2022)
ABSTRACTThis research aims to analyze the doses response of Azolla microphylla compost and husk charcoal on the growth and yield of shallot (Allium ascalonicum L.) Bima Brebes. The research was conducted for two months at KP3 Bandongan, Faculty of Agriculture, Universitas Tidar. The research was arranged on Randomized Complete Block Design (RCBD) with the first factor was husk charcoal dosage (0; 21; 31; and 42 g/polybag) and the second factor was the dose of A.microphylla compost (21; 31; 42; and 52 g/polybag). The results showed that the husk charcoal dose of 20 g/polybag induced the highest average weight dry roots. The low nutrient content in A.microphylla compost caused compost to not be able to act as a biofertilizer so the growth and yield of shallots were not optimal. The interaction of the two treatments did not give a positive response so the growth of roots and tubers in this study was smaller, which was less than 5 grams. High rainfall during the study caused the addition of husk charcoal as a soil improver and A.microphylla compost as a source of plant nutrients were not able to increase the growth and yield of the Bima Brebes shallots. Keywords: husk charcoal dosage, A.microphylla compost, shallots bulbs